Respect and Struggles for Recognition: Kant and Honneth - Salman, Selda (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Philosophers and scholars often overlook Kant’s foundational contribution to the concept of recognition (Anerkennung), yet it proves challenging to develop a comprehensive theory without integrating Kantian moral philosophy, particularly his conceptualization of respect. I contend that the demand for recognition necessitates a Kantian moral perspective, which revolves around the feeling of respect. In this regard, I draw upon the insights of contemporary philosopher Axel Honneth, who acknowledges the influence of Kant’s moral philosophy in shaping the conceptualization of the struggle for recognition.